Estimation of the number of pigeons (Columba livia) in two urban areas of Metropolitan Lima through the application of point count methods and strip transects - Ventura P., Mayra (2023)
The study’s objective was to estimate the number of pigeons (Columba livia) in two urban spaces in the metropolitan area of Lima by applying point count methods and strip transects. For this purpose, two parks were chosen, one in the district of Los Olivos and the other in Comas. The park’s area was measured and divided into point counts and strip transects. The evaluation of each method was conducted three times a day for six days. Data were summarized using descriptive statistics, and contrasts were made using the Mann-Whitney U test and Kruskal Wallis. The census methods provided statistically comparable results. The point count method allowed a detailed evaluation of the association with pigeon habitat and elucidation of why pigeons cluster in a particular study area. On the other hand, the strip transect method allowed obtaining the information in a shorter time. The information from the study allows us to have a reference of the initial population in both parks, establishing measures to evaluate the control methods of the municipalities to reduce the population of these birds.